2011
DOI: 10.1140/epjb/e2011-20395-3
|View full text |Cite
|
Sign up to set email alerts
|

Velocity autocorrelation function of a Brownian particle

Abstract: In this article, we present molecular dynamics study of the velocity autocorrelation function (VACF) of a Brownian particle. We compare the results of the simulation with the exact analytic predictions for a compressible fluid from [6] and an approximate result combining the predictions from hydrodynamics at short and long times. The physical quantities which determine the decay were determined from separate bulk simulations of the Lennard-Jones fluid at the same thermodynamic state point.We observe that the l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 25 publications
1
28
0
Order By: Relevance
“…In recent years, Brownian motion of spherical particles with uniform wettability was extensively studied by MD simulations [19][20][21][22][23][24][25][26]. It was shown that a number of parameters, e.g., the mass and size ratios of a particle and a solvent molecule, interaction potentials, boundary conditions and the system size, can influence the diffusion process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, Brownian motion of spherical particles with uniform wettability was extensively studied by MD simulations [19][20][21][22][23][24][25][26]. It was shown that a number of parameters, e.g., the mass and size ratios of a particle and a solvent molecule, interaction potentials, boundary conditions and the system size, can influence the diffusion process.…”
Section: Introductionmentioning
confidence: 99%
“…However, if the particle consists of a cluster of atoms and their interaction energy with fluid molecules is sufficiently large, then stick boundary conditions apply at the particle surface [23,25].…”
Section: Introductionmentioning
confidence: 99%
“…The initial momentum of a tagged atom can also be rapidly carried away by propagating sound waves. Usually, this contributes only to the short time decay of the VAF [19]. As the system is confined, the long-time hydrodynamic tail is expected to be lost and this mechanism becomes important.…”
mentioning
confidence: 99%
“…However, introducing compressibility in continuum hydrodynamics [27,28] does not improve the prediction for the VACF, even with an effective hydrodynamic radius adjusted to reproduce the calculated friction (see [19]), because it does not capture molecular scale effects. Finally, let us consider the implications of the present work for larger solutes.…”
Section: Figmentioning
confidence: 99%